Peran Etika Bisnis dalam Meningkatkan Citra pada Toko Online Alvasix (International Forum of Researchers and Lecturers, 2025)
Ethics in the business world is an important factor that every business entity, including online stores, must possess. The application of business ethics can shape a positive image and increase public trust in a business. This study discusses the role of business ethics in improving the image of the online store Alvasix. Observational results indicate that the online store Alvasix has implemented principles of business ethics, such as providing clear and honest product information, maintaining transparency in transactions, and displaying professionalism through friendliness, social responsibility, and prompt service to customers. With the implementation of good ethics, the online store Alvasix has successfully built customer trust, which indirectly impacts the overall improvement of the business image.